The relationship between age and fitness profiles in elite male ice hockey players - Vigh-Larsen, J. F.; Haverinen, M. T.; Knudsen, C. B.; Daasbjerg, A.; Beck, J. H.; Overgaard, K.; Mohr, M.; Andersen, T. B. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The present study investigated relationships between age, body composition and performance in elite male ice hockey players. METHODS: 199 players performed off-ice tests (countermovement jump height (CMJ) and body composition) and on-ice tests (5-10-5 Pro Agility test, 30-m sprint test and the maximal Yo-Yo Intermittent Recovery Ice Hockey test (Yo-Yo IR1-IHMAX) for assessment of aerobic capacity. RESULTS: No overall correlations between age and performance were present except small-moderate positive associations between age and body- and muscle mass (r=0.24-0.30, P=0.05). The youngest age group (YOU; 18-21 years) were 4-9% lighter than all other age groups and possessed 7% less muscle mass compared to the oldest players (OLD; 30-33 years) (P=0.05), whereas no differences were present in body fat percentage. OLD were 2-3% inferior to the second youngest (SEC; 22-25 years) and mid-age group (MID; 26-29 years) in sprint and agility performance in addition to a 6-10% lower CMJ height (P=0.05). The younger age groups differed only by a 7 and 5% better CMJ performance in MID compared to YOU and SEC, respectively (P=0.05). In contrast, no differences were found in distance covered on the Yo-Yo IR1-IHmax. CONCLUSIONS: Only small-moderate associations between age and body composition were present unlike for the remaining performance parameters. Nevertheless, a consistently lower high-intensity exercise performance was evident in the oldest- and a lower body weight in the youngest players, whereas aerobic capacity was similar. This suggests that capabilities related to size, strength and power are the most critical parameters differing between young and old ice hockey players.